Opioid exposure after injury in United States trauma centers: A prospective, multicenter observational study. Issue 6 (June 2020) - Harvin, John A.; Truong, Van Thi Thanh; Green, Charles E.; Allen, LaDonna; Murry, Jason; Radosevich, John J.; Bogert, James N.; Murphy, Patrick B.; Padilla-Jones, Brandy B.; Zarzaur, Ben L.; Taylor, John R.; Sexton, Kevin W.; et al.
Abstract : BACKGROUND: Efforts to reduce opioid use in trauma patients are currently hampered by an incomplete understanding of the baseline opioid exposure and variation in United States. The purpose of this project was to obtain a global estimate of opioid exposure following injury and to quantify the variability of opioid exposure between and within United States trauma centers. STUDY DESIGN: Prospective observational study was performed to calculate opioid exposure by converting all sources of opioids to oral morphine milligram equivalents (MMEs). To estimate variation, an intraclass correlation was calculated from a multilevel generalized linear model adjusting for the a priori selected variables Injury Severity Score and prior opioid use. RESULTS: The centers enrolled 1, 731 patients. The median opioid exposure among all sites was 45 MMEs per day, equivalent to 30 mg of oxycodone or 45 mg of hydrocodone per day. Variation in opioid exposure was identified both between and within trauma centers with the vast majority of variation (93%) occurring within trauma centers. Opioid exposure increased with injury severity, in male patients, and patients suffering penetrating trauma. CONCLUSION: The overall median opioid exposure was 45 MMEs per day. Despite significant differences in opioid exposure between trauma centers, the majority of variation was actually within centers. This suggests that efforts to minimize opioid exposure after injury should focus within trauma centers and not on high-level efforts to affect all trauma centers. LEVEL OF EVIDENCE: Epidemiological, level III. Abstract : Supplemental digital content is available in the text.